A Novel Power Series Method for Solving Second Order Partial Differential Equations - Kurulay, Muhammet; Bayram, Mustafa (EUROPEAN JOURNAL PURE & APPLIED MATHEMATICS, 2009)
In this article, a new approach is proposed to solve partial differential equation. This method is based on generalized Taylor's formula. The solution of partial differential equations can be expanded using MAPLE. Doing some simple mathematical operations on these equations, we can get a closed form series solution or approximate solution quickly. PDE problems with constant and variable coefficients are solved by the present method. With this method, we can reach same results simpler way than other analytical or approximate methods.
Keywords: Second order partial differential equations; Power Series; Mathematics